Treatment of chikungunya-associated joint pain: a systematic review of controlled clinical trials. (6th June 2022) - Rodrigo, Chaturaka; Herath, Tharuka; Wickramarachchi, Uchila; Fernando, Deepika; Rajapakse, Senaka
Abstract: Post-chikungunya joint pain (arthritis or arthralgia) is a clinical concern in endemic regions as it may cause a debilitating illness sometimes years after the acute infection. This systematic review analyses evidence from controlled clinical trials regarding the efficacy of pharmacological and non-pharmacological interventions to treat post-chikungunya joint pain. PubMed, EMBASE, Scopus, Cochrane library and Web of Science were searched for eligible studies without any language or time limits, excluding retrospective studies, and prospective observational studies without a control group. Eleven studies met the inclusion criteria. Seven assessed pharmacological interventions and four assessed non-pharmacological interventions (exercise, neuromodulation). The number of participants in each intervention arm varied from 10 to 75 and, given the heterogeneity of interventions, a meta-analysis was not possible. Available evidence does not show any added benefit of chloroquine, hydroxychloroquine, stand-alone methotrexate or ribavirin compared with anti-inflammatory drugs or placebo/no treatment. Non-steroidal anti-inflammatory drugs may reduce pain up to 24 wk of treatment but long-term residual impact after stopping treatment is unassessed. Currently, there is also no high certainty evidence to recommend non-pharmacological methods such as exercise and neuromodulation.